Shoe design : A handbook for footwear designers (Hong Kong : Fashionary International, 2021)
Differing from ordinary shoe design books, this is a complete handbook geared towards practical usage by footwear designers. It includes three main sections: Shoe Style Library, Shoe Encyclopaedia, and Shoe Templates for Tracing. The first section features more than 300 styles of shoes, ranging from historical archetypes to the most signature styles in todays footwear industry. The second focuses on essential and practical information on shoe design, from materials and construction to labels and international fairs. The templates section includes both basic templates and templates for 60 styles of common footwear, from flats and boots to high heels.
Keywords: Ontwerpen